The Manchester operation – is it time for it to return to our surgical armamentarium in the twenty-first century?. (4th July 2022) - Gold, Ronen S.; Amir, Hadar; Baruch, Yoav; Gordon, David; Shimonov, Mordechai; Groutz, Asnat
Abstract: We conducted a study to assess the efficacy and outcome results of Manchester operation for women with symptomatic elongation of uterine cervix between 2010 and 2020. Forty-five women were enrolled. Mean age was 54.2 ± 10.5 years, 57.5% were premenopausal. Mean follow up was 4.53 years. Most patients were pleased from the surgery: 29 (76.3%) very pleased and three (7.9%) quite pleased. There were four cases of late postoperative complications: hematometra, pyometra, vesicovaginal fistula and small bowel evisceration through the posterior vaginal fornix. All four cases required surgical interventions with complete recovery. Manchester operation is an effective procedure for symptomatic elongation of uterine cervix. The surgery is short, minimal blood loss and without significant intraoperative complications. However, it is not free of late postoperative complications and it is therefore important that the surgery will be carried out with a strict technique and by skilled surgeons who are capable to manage unique postoperative complications. Impact Statement: What is already known on th is subject? Elongation of the uterine cervix is a condition that has not been sufficiently studied. Up-to-date data regarding the efficacy and safety of the Manchester operation for patients with cervical elongation and normal pelvic support are scarce, as most previously published studies included mainly patients with uterine prolapse. What do the results of this study add? The present study presents the efficacy, complications and clinical outcomes of Manchester operation for women with elongation of the uterine cervix. Our results show that Manchester operation is safe, effective method for symptomatic uterine cervix elongation. What are the implications of these findings for clinical practice and/or further research? This suggests Manchester operation is an effective procedure for symptomatic uterine cervix elongation should be implemented more widely. It must be carried out with a strict technique by skilled surgeons capable to manage unique postoperative complications.